Pola Peresepan Obat Glaukoma Di Poli Spesialis Mata Rumah Sakit X Di Kabupaten Sidoarjo Periode Desember 2022 – Februari 2023 - nur halimah; Yugo Susanto (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2023)
Abstract Glaucoma is a chronic optic neuropathy disease characterized by occlusion of the optic disc, narrowing of the field of view, and increased intraocular pressure. The purpose of this study was to determine the pattern of glaucoma medication adherence in the ophthalmology polyclinic of Hospital X in Sidoarjo Regency for the period December 2022 - February 2023. This study was descriptive, non-experimental, and retrospective data collection. The results of this study obtained 127 prescription sheets . Based on the gender, there were 94 women (74.04%) and 33 men (25.98%). The most common age group suffered by patients aged over 65 years were 44 people (34.65%). There are 3 groups that are most widely prescribed, namely the non-selective Beta blocker group (Timolol 0.5% eye drops) obtained 63 prescriptions (49.61%) with the rule of daily use 2 x 1 drop, the Systemic Carbonic Anhydrase Inhibitor group (Acetazlamde 500 mg tablets ) obtained 9 prescriptions (7.09%) with the rule of daily use 1 to 2 times 1 tablet, the Prostaglandin Analog group (Latanaprost 0.005% eye drops) obtained 4 prescriptions (3.15%) with the rule of using 1 drop at night. Prescribing pattern for glaucoma drug that was most often prescribed was Timolol 0.5% eye drops obtained 63 prescriptions (49.61%).